Data resource profile: The ZEW FMS dataset - Frank Brückbauer; Michael Schröder (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
The ZEW Financial Market Survey is a monthly panel survey among financial market experts that was launched in December 1991. The survey focuses on the experts' expectations about international financial markets and macroeconomic developments. We describe the ZEW Financial Market Survey and the resulting research dataset, which 1) is available for free for academic researchers, 2) is large and includes long individual time series (99,001 responses by 2,002 respondents, as of September 2021), and 3) contains rich information on the financial market experts collected over the years and which can be combined with the data on expectations. We give a detailed overview of the academic publications based on ZEW FMS data and provide information on how to access the dataset.
Keywords: C8; D84; G17; G4; 330; research dataset; financial market experts; financial market expectations